2022
DOI: 10.3390/antibiotics11121712
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and In Vitro and In Silico Antileishmanial Evaluation of the Essential Oil from Croton linearis Jacq. Stems

Abstract: Croton linearis Jacq. is an aromatic shrub that has been utilized in traditional medicine in the Bahamas, Jamaica, and Cuba. Recent studies have revealed the antiprotozoal potential of its leaves. The present work is aimed to identify the volatile constituents of essential oil from the stems of C. linearis (CLS-EO) and evaluate its in vitro antileishmanial activity. In addition, an in silico study of the molecular interactions was performed using molecular docking. A gas chromatographic–mass spectrometric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Regarding α-pinene, the in silico study aligns with previous experimental results, indicating its weak interaction with lanosterol demethylase (binding energy of −5.5 kcal/mol). In fact, a previous study outlined a similar affinity reporting a binding energy of −5.63 kcal/mol [47]. However, it should be noted that the leishmanicidal activity of α-pinene is explained by a different mechanism of action.…”
Section: Discussionmentioning
confidence: 65%
“…Regarding α-pinene, the in silico study aligns with previous experimental results, indicating its weak interaction with lanosterol demethylase (binding energy of −5.5 kcal/mol). In fact, a previous study outlined a similar affinity reporting a binding energy of −5.63 kcal/mol [47]. However, it should be noted that the leishmanicidal activity of α-pinene is explained by a different mechanism of action.…”
Section: Discussionmentioning
confidence: 65%
“…A study by Setzer and coworkers reported the chemical characterization and in vitro and in silico antileishmanial evaluation of the essential oil (EO) from Croton linearis Jacq. stems (CLS-EO) [5]. Croton linearis is an aromatic shrub with a history of traditional medicinal use in the Bahamas, Jamaica, and Cuba, known for its antiprotozoal properties.…”
mentioning
confidence: 99%